PENGARUH PROFITABILITAS, LEVERAGE, DAN SUSTAINABILITY DISCLOSURE TERHADAP NILAI PERUSAHAAN SEKTOR ENERGI DI BURSA EFEK INDONESIA TAHUN 2020–2023 - Upriani, Upriani; Anwar, Anwar; Nurman, Nurman; Musa, Muh Ichwan; Aslam, Annisa Paramaswary (Jurnal Manajemen dan Bisnis, 2026)
This study examines the effect of profitability, leverage, and sustainability report disclosure on firm value in energy sector companies listed on the Bursa Efek Indonesia during the 2020–2023 period. The increasing demand for sustainability transparency and environmental, social, and governance (ESG) practices has encouraged companies to improve financial performance and sustainability disclosure to enhance firm value. This research employed a quantitative explanatory approach using panel data regression analysis. The population consisted of energy sector companies listed on the stock exchange, with 16 companies selected through purposive sampling. Secondary data were obtained from annual and sustainability reports. Data analysis was conducted using EViews 13 software. The results indicate that profitability and leverage have a positive and significant effect on firm value. Meanwhile, sustainability report disclosure does not significantly affect firm value. Simultaneously, profitability, leverage, and sustainability disclosure significantly influence firm value. These findings provide insights for investors and corporate management regarding the importance of financial performance and sustainability disclosure in enhancing firm value